The Blockchain Technology and Its Limitations for True Disruptiveness of Accounting and Assurance - Atanasovski, Atanasko; Trpeska, Marina; Bozhinovska lazarevska, Zorica (ASERS Publishing, 2020)
Blockchain is distributed ledger technology praised by many tech savvy executives to disrupt and change many businesses in the future, including the accounting and assurance profession. This study critically assesses the disruptive potential of the technology for modern accounting information systems and accounting professionals. It summarizes limitations and constraints of the technology through qualitative research of academic literature, professional documents and tech websites. The study discusses scalability, transaction costs, interoperability and confidentiality issues as most significant constraints for accelerated adoption and deployment of blockchain based accounting information systems. The economic case of blockchain based accounting information system, real cases of practical implementation and appropriate governance structures are suggested as important areas for future research efforts.
Keywords: blockchain; accounting; smart contract; distributed ledger; disruptive technology